Prevalence of hearing problems and associated factors in an agricultural company in southern Brazil - Rafael Haeffner; Leila Maria Mansano Sarquis; Rita Maria Heck; Vanda Maria da Rosa Jardim (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: To describe the prevalence and to analyze the factors associated with hearing problems in an agricultural company. METHODS: This was a cross-sectional study, and the participants consisted entirely of employees of an agricultural company in southern Brazil. The workforce of the company was composed of several different occupations. The research instrument was a semi-structured questionnaire administered by interview. RESULTS: Of the 326 workers of the company, there were 273 (83.8%) respondents, and the prevalence of hearing problems was n = 42 (15.4%) among the participants of the study. The hearing problems were associated with lower schooling, with the operating occupational group, the technical assistance group and the general services group. The self-reported health conditions associated with hearing problems were depression and nervousness or irritation. The occupational exposures associated with hearing problems were noise, dust, vibration, oils and solvents, and toxic gases. CONCLUSION: There was an intermediate prevalence of hearing problems in relation to other studies. It was possible to observe the need to implement strategies aiming at the prevention of hearing problems that primarily contemplate modifiable aspects, such as the use of personal protective equipment, as well as improvements in the conditions, organization and work environment.